Investigating sexuality in adolescents with cancer: patients talk of their experiences. (2nd April 2020) - Veneroni, Laura; Bagliacca, Elena Pagani; Sironi, Giovanna; Silva, Matteo; Casanova, Michela; Bergamaschi, Luca; Terenziani, Monica; Trombatore, Jessica; Clerici, Carlo Alfredo; Prunas, Antonio; Silvaggi, Marco; Massimino, Maura; et al.
Abstract: Objective. The aim of the present study is to understand which areas of sexuality were regarded as most important and/or problematic among adolescents with cancer. Methods. A questionnaire was administered to adolescent and young adult patients who had been receiving treatments at the Pediatric Oncology Unit of our Institution, for at least 2 months, and those in follow-up who had completed their treatments no more than two years previously. The questionnaire was devised to investigate patients' experiences in various areas, i.e. personal relations, sexual relations; functional aspects, body image, and communication. Results. Questionnaires were given to 70 patients and completed by 66. As main results, the survey showed that disease and treatment might negatively affect patients' way of relating with others (53% of cases) and their body image (56%), though their sexual desire remains unchanged (69.7%). Most patients (67%) reported not having the chance to talk to someone about having sex while receiving their treatments; 79% of patients felt this topic deserved more attention. Conclusion. This study promotes the discussion of an important topic for young people with cancer, which is inadequately addressed today. When establishing an age-specific model of care, aspects related to sexuality should be considered and managed.